ENGLISH LANGUAGE TEACHING AND EFL TEACHER PERSONALITY COMPETENCE: A BIBLIOMETRIC ANALYSIS - St. Asriati. Am; Syamsiarna Nappu; Nur Qalbi (International Conference on Humanity Education and Society (ICHES), 2023)
This study seeks to ascertain how English Language Teaching and EFL teacher personality competencies have changed between 2003 and 2022. This study is a qualitative kind with a literature study. This study employs the Scopus search engine to find studies on language teaching and teacher personality competency. VOSviewer is also used in this work to map and evaluate data. According to the study's conclusions, 2020 will see a record number of research publications. The nation that contributes the most research articles is the Russian Federation. The highest rating in publications is in teaching, articles, and communication. Furthermore, topics about communicative competence, personality category, language teacher and EFL classroom, which have great opportunities for further research, relate to the theme of English language teaching and EFL in-service teacher personality competence.